(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this study was to assess the position of impacted lower third molars, the indications for extraction, and the post-operative complications. Records of patients who attended Misan general hospital between March 2008 and April 2009 for surgical removal of mandibular third molars. The angulation type and depth of impaction were determined by reviewing the orthopantomograms. A total of 140 impacted teeth were surgically extracted from 132 patients (69 males, 63 females). The reasons for extraction include recurrent pericoronitis (55%) followed by caries (25%) and prophylactic purposes (20%). Mesioangular impactions accounted for (49.29 %) and Level 1 position of impaction accounted for (65%) of extractions. 40 complications (28.57%), including persistent pain and swelling, infection, dry socket, Trismus and ulceration were reported . Persistent pain and swelling was the most common complications followed by infection. There was no significant relationship between the angulation, level of impaction and the occurrence of complications. Mesioangular type and Level A position of impaction were the most common impaction. Although the association was not significant, high frequency of post-operative complications was observed in mesioangular, horizontal and level A position of impaction.